The Study of Characteristic of Eco-Friendly Geotextile based on Low-Density Polyethylene (LDPE) Plastic Bag Waste - SAHREL, ERRA SAFFIRRA; Marsi, Noraini (Progress in Engineering Application and Technology, 2021)
: The study presents the utilization of plastic bag waste reinforced geotextile. The objective of this research is to determine the optimum layer of Low-Density Polyethylene (LDPE) plastic bag waste to produce geotextile. This study is involved the different layers of LDPE plastic bag waste which are 4 layers, 6 layers, 8 layers, 10 layers, and 12 layers by using a hot press process with 120°C and 140°C temperatures. LDPE plastic bag wastes were cut with dimensions of 270 mm width x 400mm length. Then, the samples were cut into pieces to evaluate their physical and mechanical properties. For physical properties test, samples shows that the nitrile group is identified at sample of 10 layers of LDPE plastic bag waste after heat treatments of 120°C. The 12 layers of LDPE plastic bag waste that undergo 140°C has highest thickness of 0.3712mm. The rougher surface was found on 12 layers of LDPE plastic bag waste that undergo 140°C in optical microscopy test. For the mechanical properties test, the 10 layers of LDPE plastic bag waste that undergoes 120°C withstood the highest elongation at break at 490.02mm and highest percentage strain at break at 653.36. The 12 layers of LDPE plastic bag waste that undergo 120°C has highest burst strength with 8.55kgf. The 12 layers of LDPE plastic bag waste that undergo 140°C has highest coefficient of friction with 0.585. In a nutshell, the study found that 10 layers of LDPE plastic bag waste that undergoes 120°C are suitable for eco-friendly geotextile.